Defining pollen exposure times for clinical trials of allergen immunotherapy for pollen-induced rhinoconjunctivitis - an EAACI position paper - Pfaar, Oliver (Allergy, 2017)
Background Clinical efficacy of pollen allergen immunotherapy (AIT) has been broadly documented in randomized controlled trials. The underlying clinical endpoints are analysed in seasonal time periods predefined based on the background pollen concentration. However, any validated or generally accepted definition from academia or regulatory authorities for this relevant pollen exposure intensity or period of time (season) is currently not available. Therefore, this Task Force initiative of the European Academy of Allergy and Clinical Immunology (EAACI) aimed to propose definitions based on expert consensus. Methods A Task Force of the Immunotherapy and Aerobiology and Pollution Interest Groups of the EAACI reviewed the literature on pollen exposure in the context of defining relevant time intervals for evaluation of efficacy in AIT trials. Underlying principles in measuring pollen exposure and associated methodological problems and limitations were considered to achieve a consensus. Results The Task Force achieved a comprehensive position in defining pollen exposure times for different pollen types. Definitions are presented for ‘pollen season’, ‘high pollen season’ (or ‘peak pollen period’) and ‘high pollen days’. Conclusion This EAACI position paper provides definitions of pollen exposures for different pollen types for use in AIT trials. Their validity as standards remains to be tested in future studies.
Published online: 22 November 2016
Gesehen am 16.08.2018